MEMBERDAYAKAN EPISTEMOLOGI PENDIDIKAN ISLAM - Raudhatuz Zahrah (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
Islamic education must be built and developed based on epistemology to create quality and highly competitive Islamic education to survive and lead. Efforts to explore, discover and establish Islamic education can be effective and efficient if it is based on the epistemology of Islamic teaching. So that the development of Islamic education conceptually and in an applicative manner must be built from the epistemology of Islamic education as a whole. So the epistemology of Islamic education emphasizes efforts, ways, or steps to gain knowledge of Islamic teaching. The activity of thinking in epistemology is the most capable of developing scientific creativity compared to ontology and axiology. Epistemology of Islamic education is an object of knowledge, a way of obtaining knowledge and a way of measuring the correctness of knowledge related to the formation of personality, morals, developing nature and all human potential to the fullest so that they become a good Muslim, have a logical-critical mindset, have faith, fear, and are helpful. For themselves and their environment, they can achieve happiness in this world and the hereafter, according to Islamic teachings